A preliminary investigation into psychosocial outcome and quality-of-life in adolescents following childhood traumatic brain injury. (July 2013) - Green, L.; Godfrey, C.; Soo, C.; Anderson, V.; Catroppa, C.
Abstract Objective: This study investigated the long-term psychosocial outcome and quality-of-life (QoL) of 15–18 year olds, sustaining childhood traumatic brain injury (TBI) between birth and 5 years. Method: Thirty-three participants (17 TBI parent-proxies, 16 control parent-proxies) were involved in the present study which compared parent-ratings for the TBI group and healthy controls on the Sydney Psychosocial Reintegration Scale–Child form (SPRS-C) and the Paediatric Quality of Life Inventory (PedsQL). Results: Despite comparable overall psychosocial reintegration scores, parents reported that their teens with TBI were more likely to experience poor QoL compared to controls. On further analysis, some aspects of psychosocial outcome appear to be compromised following childhood TBI. Conclusions: Interventions targeting childhood TBI must consider QoL in addition to symptom reduction and be extended throughout adolescence. The limitations of the sample size are cause for concern; however, preliminary results do validate the need for future research efforts.